Work of indentation approach to the analysis of hardness and modulus of thin coatings - Korsunsky, A; Constantinescu, A (Elsevier, 2006)
The problem of accurate identification of mechanical properties, primarily hardness and modulus, invariably arises whenever very thin coatings are considered that consist of single or multiple layers, e.g. in the context of fitness-for-purpose characterisation of coated systems, monitoring in-service degradation, component lifetime prediction, etc. Rapid developments in the areas of nano-fabrication, nano-manipulation and nano-technology lead to the increased importance of reliable characterisation of mechanical properties of progressively thinner coatings. Instrumented small scale (nano-) indentation is particularly well-suited to surface-engineered and thin-coated systems. The present study presents a review and refinement of the interpretation techniques for instrumented (nano) indentation for reliable property de-convolution of coated systems. Particular attention is devoted to contact modulus and hardness, as the properties that play the key role in controlling the deformation reponse of any surface, and affect such service properties as impact and erosion resistance, wear and fretting fatigue resistance, resistance to crack initiation and propagation, etc. A flexible multi-scaling power law functional description is introduced and discussed, and its application to various example systems is illustrated.